Frijol: fisiologia del potencial de rendimiento y tolerancia al estres - White, Jeffrey W.; Izquierdo, J. (Oficina Regional de la FAO para América Latina y El Caribe, 1989)
A descriptive and integrated look at the physiology of the bean plant is presented. Initially, the basic physiological processes that determine bean yields are discussed, namely (1) metabolic events such as photosynthesis, respiration, and N metabolism, which have a direct effect on growth, and (2) morphogenic events, such as germination, vegetative and reproductive growth, senescence and abscission, which affect the change in form or development of the plant. The integration of these processes through carbohydrate and N partitioning is reviewed as well as the source-sink model, information that is then applied to yield potential and stress tolerance. Specific physiological strategies for increasing yields considering both source (photosynthesis, respiration, light utilization) and sink capacities (flower, seed, and pod abortion, pod growth rates, HI) are reviewed. An ideotype for max. yield is proposed. The problems of earliness and seed size, and several nonconventional strategies are discussed; abiotic stresses that affect yield potential, such as drought and excess water, and rusticity in beans are also analyzed. Unpublished results obtained in research work in Latin America are included to illustrate physiological phenomena not considered in previous studies. Indications are that bean crop productivity can be improved only through 2 basic approaches: (1) modifying plant genotypes to fit the environment better and (2) changing the environment to ameliorate the effects of environmental stresses. The need for further research on the role of N remobilization in leaf senescence and seed growth is evidenced. (CIAT)